Tracking genome-editing and associated molecular perturbations by SWATH mass spectrometry - Lin, Qifeng (2020)
Advances in gene editing now allow reverse genetics to be applied to a broad range of biological systems. Ultimately, any modification to coding sequences requires confirmation at the protein level, although immunoblotting is often hampered by antibody quality or availability especially in non-model species. Sequential Window Acquisition of All Theoretical Spectra (SWATH), a mass spectrometry (MS) technology with exceptional quantitative reproducibility and accuracy, offers an ideal alternative for protein-based confirmation. Here, using genome edits in mouse, zebrafish and Bicyclus anynana butterflies produced using either homologous recombination or targeted nucleases, we demonstrate absence of the targeted proteins using SWATH, thus confirming successful editing. We show that SWATH is a robust antibody-independent alternative for monitoring gene editing at the protein level and broadly applicable across diverse organisms and targeted genome manipulation techniques. Moreover, SWATH concomitantly defines the global proteome response in the edited organism, which may provide pertinent biological insights.